PREVALENCE OF WORK RELATED MUSCULOSKELETAL DISORDERS AMONG PHYSICIANS, SURGEONS AND DENTISTS AT TERTIARY CARE HOSPITALS OF PESHAWAR - Zeb, Alam; Ali, Wajid; Darain, Haider; Rahman, Mujeeb Ur (Annals of Allied Health Sciences, 2017)
Objective: To determine prevalence of work related musculoskeletal disorders among physicians, surgeons and dentists. Methods: A cross-sectional study was conducted at tertiary care hospitals of Peshawar Khyber Pakhtunkhwa. A total to 300 questionnaires were distributed amongst the participants. Questionnaires were given to 100 Physicians, 100 Surgeons and 100 Dentists working at tertiary care hospitals of Peshawar. Positive responses from physicians, surgeons and dentists were 87, 84 and 89, respectively. Questionnaire consists of two sections involving demographic characteristics and Modified Nordic questionnaire. SPSS version 20 was used for data analysis. Results: The prevalence of WRMDs was highest among dentists 69% (55/80) followed by Surgeons 53% (42/80) and physician’s 39% (31/80).Low back, neck and shoulder were the main complaint areas. Conclusion: MSDs are multi-dimensional relating to various risk factors involving prolonged Static postures, repetitive tasks, awkward and cramp positions, inadequate training physical conditioning, age and obesity. There is significant relation of MSDs with BMI and gender of Participants. WRMDs shows significant burden for health professional’s therefore proper Attention and preventive measures should be taken to minimize this problem.